The Effectiveness of The Role, Audience, Format and Topic (RAFT) Technique on Students’ Skill in Writing Expository Text - Suciati, Suciati (Institut Agama Islam Negeri Kudus, 2018)
This research examines the effectiveness of RAFT and conventional technique in improving high and low motivated students’ skill in writing expository text and explained the motivation interaction to their skill. RAFT is a system to help students understand their role as a writer, audience, varied formats for writing, and expected content. This research uses factorial design with 36 students of experimental group and 34 in control group. They are eleventh graders of MA Tarbiyatul Banin, Winong-Pati. The result shows that RAFT is effective in improving the high and low motivated students’ skill in writing expository text on the level of significance 0.05, the conventional technique is effective in improving the high and low motivated students’ skill in writing expository text on the level of significance 0.05. There is interaction of the students’ motivation to students’ skill in writing expository text using RAFT and conventional technique. By using RAFT, the high motivated students’ skill get more improvement and by using conventional technique, the low motivated students’ skill get more improvement. Further, the use of RAFT in improving the students’ skill in writing expository text is more effective than the use of conventional technique.